Flotation separation and interfacial interaction mechanisms of millimeter-scale Cu/Al foils from spent lithium-ion batteries - Yongwei Wang; Lijue Wang; Shen’ao Zhang; Junhui Chen; Junwei Han (Minerals Engineering, 2026)

Interconnected microporous carbon enabling boosted electrode-scale kinetics in dense supercapacitor electrodes - Qiqi Li; Su Zhang; Yutong Li; Junwei Han; Zhiyuan Li; Wei Xing; Han Hu; Luxiang Wang; Nannan Guo; Ning Cao (Chemical Engineering Journal, 2026)

Pyrolysis kinetics and evolution mechanism of gaseous products of polyvinylidene fluoride and polyolefin separator - Yongwei Wang; Zecong Lu; Na Zhang; Shen’ao Zhang; Junhui Chen; Junwei Han (Journal of Environmental Chemical Engineering, 2026)

Sulfidation of copper oxide with CaSO4 for copper flotation: Experimental study and first-principles calculation - Xuesong Gao; Siwen Tan; Yongwei Wang; Kunhong Gu; Xinglan Cui; Junwei Han (Journal of Environmental Chemical Engineering, 2026)

Synergistic bimetallic catalysis and heterointerface engineering in MgFe LDH-biochar enhancing non-radical-dominated antibiotic degradation - Jie Ren; Mengfan Li; Han Sun; Ruosong Jing; Junwei Xin; Xudong Wang; Yongtao Lv; Licheng Chen; Danxi Huang; Lei Wang (Journal of Environmental Chemical Engineering, 2026)

Microbial community succession, functional dynamics, and fermentative characteristic of yeasts in the fermented grains of strong-flavor Baijiu - Qingqing Li; Huafang Feng; Junwei Wang; Lang Han; Jinshan Li; Yongmei Hu; Nan Peng; Shumiao Zhao (Food Research International, 2026)

A konjac glucomannan-based hydrogel delivery system induces trained immunity via enhanced oxidative phosphorylation for improved vaccine protection - Zheng Jia; Yadong Gao; Husile Han; Chaonan Wang; Jiaqing Wang; Junjie Guo; Shuhe Zhang; Yifan Li; Junwei Ge; Fang Wang; Mingchun Gao (Carbohydrate Polymers, 2026)

Anthropogenic or climate-driven? Mechanisms of the AD 1642 extreme flood Disaster of the Yellow River in Ancient Kaifeng, China - Junjie Shen; Aishan Han; Panpan Chen; Junwei Wan; Mengdie Zhao; Mingming Jia; Yan Tian; Peng Zhang; Huayong Li; Qianyu Tang; Peng Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

TCEP induces liver injury through suppression of the PI3K/AKT axis: Integrated evidence from epidemiology, network toxicology, and In vivo validation - Jianing Sun; Han Zhu; Yan Yan; Wenru Wang; Junwei Gao; Peng Liu (Chemico-Biological Interactions, 2026)

Synergistic remediation of cadmium-contaminated soil by biochar-cement-plant system: performance and underlying mechanism - Suyun Meng; Liulan Zhong; Wenlong Han; Shiwei Hou; Lei Lang; Junwei Zhang (Journal of Soils and Sediments, 2026)

Chemical constituents from the n-Butanol extract of Senecio scandens Buch. - Ham and their chemotaxonomic significance - Chunshan Ke; Liang Lai; Chuanqi Xie; Junwei Xu; Zhiyong Xu; Yunfei Liu; Yongsheng Guo; Xiaodan Han; Wei Xiong; Lei Wu; Hongxu Li (Biochemical Systematics and Ecology, 2026)

Red phosphorus triggers endogenous iron activation of sludge biochar for peroxymonosulfate activation: Unravelling superoxide radical and non-radical degradation mechanisms - Minghui Xiang; Zhikang Deng; Yongfei Ma; Yifan Liu; Xiaoyu Xiang; Han Ding; Ranran Zhang; Hui Lin; Junwei Ma; Yongzhen Ding; Zulin Zhang (Journal of Environmental Chemical Engineering, 2026)

Fermented red quinoa (FRQ) effectively mitigates chronic alcohol-induced cognitive impairment and hepatic steatosis through multi-mechanistic pathways - Zi-Han Lin; Zhaohui Wang; FenFen Wei; Xinyao Zhu; Junwei Ma; Yan Wu; Song-Mei Chen; Li-Hua Song (Food Research International, 2026)

Mechanochemical dual-functional interface via in-situ polymerization for high-performance silicon-based quasi-solid-state batteries - Mingxue Zuo; Xia Hu; Bocheng Yang; Guanzhong Ma; Shaohui Shi; Xin Qin; Changzhi Ji; Junwei Han; Debin Kong; Linjie Zhi (Chemical Engineering Journal, 2026)

Calcium chloride enhanced integrated pyrolysis and selective metal extraction from spent lithium batteries - Yongwei Wang; Shen’ao Zhang; Xinglan Cui; Junwei Han (Journal of Environmental Chemical Engineering, 2026)

Amino-modified gangue-derived NaX zeolite for enhanced stabilization of lead and cadmium in contaminated soils: synthesis, performance, and leaching stability - Weiwei Zhu; Jingyi Xiong; Zhuoxi Huangfu; Jiang Yu; Pengxinyue Hang; Cheng Han; Ming Chen; Bin Li; Tao Gao; Junwei Yang; Yao Du (Environmental Geochemistry and Health, 2026)

9-Methylstreptimidone: A novel promising fungicide disrupting material metabolism and energy synthesis in Colletotrichum orbiculare - Wenshuai Song; Jingzheng Sun; Haifeng Zhang; Han Wang; Lifeng Guo; Xiaoya Fan; Xi Xu; Kun Zhang; Hongbo Pang; Xiangjing Wang; Junwei Zhao; Wensheng Xiang (Pesticide Biochemistry and Physiology, 2025)

Basalt visible light image recognition optimization algorithm based on YOLOv8 - Fen Jiao; Yu Yin; Xiangchuan Min; Congren Yang; Junwei Han; Qian Wei; Limin Tang; Ying Huang; Wenqing Qin (Minerals Engineering, 2025)

Efficient separation of copper and aluminum foils from spent lithium-ion batteries via sulfidization flotation - Lijue Wang; Yongwei Wang; Shen’ao Zhang; Kunhong Gu; Junwei Han (Journal of Environmental Chemical Engineering, 2025)

Study on the mechanism of the influence of the microstructure and equivalent pore size difference of coal on methane adsorption characteristics - Xiaoming Ni; Jingshuo Zhang; Ying Han; Junwei Yuan (Chemical Engineering Journal, 2025)

Memristor-based RDBO-CNN circuit design and application of image multi-classification recognition - Gaoyong Han; Guanxiang Cheng; Yanfeng Wang; Junwei Sun (Cognitive Neurodynamics, 2025)

Efficient extraction of metals from industrial-scale pyrolytic spent LIBs materials using a leaching process without external reductants - Shen’ao Zhang; Yongwei Wang; Lijue Wang; Kunhong Gu; Junwei Han (Minerals Engineering, 2025)

Antimony-doped tin oxide/graphite composite counter electrode for hole transport layer-free printable mesoscopic perovskite solar cells with enhanced hole collection - Qiaojiao Gao; Kai Chen; Xiaoyu Li; Jiale Liu; Qian Yue; Yuan Shi; Junwei Xiang; Chuang Yang; Song Shen; Shichao Zhang; Siqi Jiang; Shijie Guan; et al. (Chemical Engineering Journal, 2025)

Harvesting of microalga Coelastrella sp. CHZ by flocculation with ionic liquid choline-alanine - Yihan Xie; Hong Gu; Benyong Han; Ximeng He; Qingming Long; Junwei Xu; Peng Zhao (Aquaculture, 2025)

Green collaborative recycling of spent NCM cathode and waste sodium sulfate via an unconventional process - Xuesong Gao; Kunhong Gu; Xinglan Cui; Junwei Han (Waste Management, 2025)

Sustainable lead extraction via sulfidation roasting of lead oxide and calcium Sulfate: Phase evolution and flotation response - Yongwei Wang; Tao Wei; Zhiwen Guan; Dakun Wang; Junwei Han (Journal of Environmental Management, 2025)

Selective extraction of lithium from industrially produced pyrolytic black powder: Thermodynamic and kinetic studies - Shen’ao Zhang; Siwen Tan; Kang Yang; Yongwei Wang; Lijue Wang; Junwei Han (Journal of Environmental Chemical Engineering, 2025)

Achieving carrier migration pathway transformation to enhance photocatalytic moxifloxacin degradation activity by regulating the Fermi Level of g-C3N4/ ZnIn2S4 through sulfur vacancies - Han Sun; Yonghao Dong; Lei Wang; Xudong Wang; Junwei Xin; Jie Ren; Ruosong Jing; Jiayuan Yan; Yichun Xue; Keyan Zhao (Journal of Environmental Chemical Engineering, 2025)

Advancing thermal treatment technologies for recycling end-of-life lithium-ion batteries - Yongwei Wang; Jiadong Yu; Duo Wang; Junwei Han; Hongbo Zeng (Chemical Engineering Journal, 2025)

Interfacial depassivation enables long-cycling silicon-based solid-state batteries without stack pressure - Lu Zhao; Junwei Han; Xin Qin; Qian Xu; Fei Yang; Junshu Sun; Pengcheng Dai; Lin Shi; Debin Kong; Linjie Zhi (Chemical Engineering Journal, 2025)

Fungal diversity associated with cherry leaf spot in Yantai city, Shandong province, China - Yumeng Wang; Ting Liu; Chuang Han; Xiaoyan Yu; Xi Xu; Yuhan Guo; Xinying He; Wensheng Xiang; Xiangjing Wang; Junwei Zhao (Physiological and Molecular Plant Pathology, 2025)

Mechano-kinetic integrated carbon coating enables fast-charging micro‑silicon anodes - Junwei Han; Xin Qin; Qian Xu; Lu Zhao; Debin Kong; Yun Cao; Fei Yang; Xia Hu; Yafei Wang; Mingxue Zuo; Huiyu Yu; Bocheng Yang; et al. (Chemical Engineering Journal, 2025)

Direct preparation of battery-grade FePO4·2H2O using iron residues via a hydrothermal process - Yuhe Cheng; Yongwei Wang; Guangjin Zhao; Junwei Han (Journal of Environmental Chemical Engineering, 2025)

Metformin alleviates cadmium-induced reproductive toxicity by enhancing mitochondrial biosynthesis and epigenetic modifications in female mice - Jiaqiao Zhu; Min Zhu; Hangbin Zhao; Yifan Lin; Xiaoxue Han; Ankai Tan; Yixian Wang; Yonggang Ma; Junwei Li; Zongping Liu (Toxicology and Applied Pharmacology, 2025)

Efficient recovery of valuable components from lithium battery cathode and silicon carbide waste based on a synergistic roasting-magnetic separation process - Yongwei Wang; Shan He; Yanyue Jia; Junhui Chen; Shen’ao Zhang; Lijue Wang; Junwei Han (Journal of Environmental Chemical Engineering, 2025)

Rhizobacterium streptomyces sp. NEAU-383 as a potential biocontrol agent to control tomato bacterial wilt - Ling Ling; Tianxin Zhao; Shanshan Zhang; Yanfang Luo; Zhengke Song; Han Wang; Wensheng Xiang; Junwei Zhao; Xiangjing Wang (Brazilian Journal of Microbiology, 2025)

Comprehensive analysis based on IFN-γ and SASP related genes, bulk RNA and single-cell sequencing to evaluate the prognosis and immune landscape of stomach adenocarcinoma - Jie Yang; Junwei Han (Genes & Genomics, 2025)

Uptake of plasmid reduces the adaptation of Shigella flexneri to disinfectants and increases transmission of antibiotic resistance genes - Xiaojun Lin; Ruiqi Han; Huishi Peng; Junwei Huang; Yanbin Xu; Qingxia Qiao; Lu Huang (International Biodeterioration & Biodegradation, 2025)

Selective adsorption of Rb+ and Cs+ by a superparamagnetic Fe₃O₄@FeMn-MOF from brine - Yanping Wang; Qiongyuan Zhang; Dezhen Fang; Kexin Li; Zhongmei Song; Wenjie Han; Junwei Li; Xiushen Ye; Haining Liu; Huifang Zhang; Xi Zhang; Zhijian Wu (Desalination, 2025)

Transitional behavior of calcareous sand with different clay contents - Hongyi Zhao; Yaru Gao; Fei Lin; Jinhai Zheng; Dong-Sheng Jeng; Shuang Han; Junwei Liu; Yifei Sun (Frontiers in Marine Science, 2025)
Calcareous sand with fines content was often encountered in offshore and onshore engineering. However, most previous research has primarily focused on the mechanical properties of clean calcareous sand. This study conducted a series of drained and undrained triaxial tests on calcareous sand-clay binary mixtures to investigate the impact of fines content on the strength and deformation characteristics of calcareous sand. The results indicate that specimens with varying fines content exhibit both strain hardening and softening behaviors under different confining pressures. With the addition of fines content from 0% to 10%, the extent of dilatancy decreases, resulting in a smaller peak friction angle compared to clean sand specimens. However, when fines content increases further to 25%, both the maximum dilatancy angle and peak friction angle show an increase. A similar trend is observed for the friction angle at the phase transition state (PTS). In the p ′ − q plane, the critical state line (CSL) remains constant despite changes in fines content, whereas in the e − p ′ 0 . 7 plane, the CSL shifts with variations in fines content. A unified CSL in the e − p ′ 0 . 7 plane can be obtained by applying the concept of equivalent skeleton void ratio. Additionally, the state dependence of the material is analyzed using both the modified state parameter and the state index. It was observed that the friction angles at both the PTS and the peak state (PS) are influenced by the state of the material, with the PTS friction angle showing a stronger correlation with the state index, while the PS friction angle is more closely linked to the state parameter.

Adaptive Discrepancy Masked Distillation for remote sensing object detection - Cong Li; Gong Cheng; Junwei Han (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Microbial desaturation experimental study of calcareous sand based on yeasts - Xiao Xie; Yumin Chen; Yi Han; Saeed Sarajpoor; Junwei Guo (Bulletin of Engineering Geology and the Environment, 2025)

Gyral peak variations between HCP and CHCP: functional and structural implications - Guannan Cao; Songyao Zhang; Zhibin He; Zifan Wang; Lei Guo; Zhiqiang Yan; Junwei Han; Xi Jiang; Tuo Zhang (Brain Structure and Function, 2025)

Semi-confining microreactor enhancing the sulfur catalysis for stable lithium-sulfur batteries - Qiuchen Song; Mengyao Li; Linkai Peng; Yun Cao; Junwei Han; Hongda Du; Wei Lv (Chemical Engineering Journal, 2025)

Vertical migration of bacteria bearing antibiotic resistance genes and heavy metal resistance genes through a soil profile as affected by manure - Junwei Liang; Yurou Han; Jian Zhao; Jiangjie He; Qizhong Huang; Yimo Zhang; Jizhen Liu; Yucheng Chen; Weihong Xu (Biology and Fertility of Soils, 2025)

Effects of fishing stress on fatty acid and amino acid composition and glycolipid metabolism in triploid rainbow trout - Banghua Xia; Dandan Zhao; Qirui Hao; Junfei Yu; Yue Han; Ling Ling; Rongwei Zhao; Junwei Zhao (Food Chemistry, 2024)

P4HA3 promotes colon cancer cell escape from macrophage phagocytosis by increasing phagocytosis immune checkpoint CD47 expression - Hailang Zhou; Junwei Zou; Jingli Han; Aijun Zhou; Shu Huang (Molecular and Cellular Biochemistry, 2024)

Intensifying the selective sulfidation of nickel in saprolitic laterites by sodium salts - Chen Li; Wei Liu; Fen Jiao; Tianfu Zhang; Junwei Han; Wenqing Qin (Minerals Engineering, 2024)

Novel nitrogen-rich hydrogel adsorbent for selective extraction of rare earth elements from wastewater - Xuyi Wei; Xiaohui Mao; Junwei Han; Wenqing Qin; Hongbo Zeng (Journal of Hazardous Materials, 2024)

Hybrid forecasting model of building cooling load based on EMD-LSTM-Markov algorithm - Xiaofei Huang; Yangming Han; Junwei Yan; Xuan Zhou (Energy and Buildings, 2024)

An unconventional approach for the efficient recovery of iron, cobalt, copper and silicon from copper slag - Yongwei Wang; Shen’ao Zhang; Lijue Wang; Wenqing Qin; Junwei Han (Journal of Hazardous Materials, 2024)

Versatile additive for enhancing the stability of Zn Anode: Pyrrolidine-based ionic liquid - Kailimai Su; Hong Zhang; Yan Wang; Xingyun Zhang; Yongbiao Mu; Zhibin Lu; Ye Han; Shanhong Wan; Junwei Lang (Chemical Engineering Journal, 2024)

Surface modification and spatial optimization of pre-lithiation TiO2 ion sieves for efficient extraction of lithium - Wenqing Qin; Jiewei Xu; Xuyi Wei; Junwei Han (Chemical Engineering Journal, 2024)

Experimental Study on Cyclic Simple Shear Test of Coastal Tidal Soft Soil - Xiuxia Yu; Honglei Sun; Junwei Liu; Hongxuan Zhao; Yu Han (Journal of Marine Science and Engineering, 2024)
Based on undrained cyclic simple shear tests conducted on coastal tidal soft soil under various conditions of cyclic stress ratios and moisture contents, this study investigated the influence of these factors on the dynamic properties of the soil. The findings indicated that with increasing moisture content and stress cycle ratio, the stress–strain hysteresis loop gradually expanded, resulting in a higher strain difference and a transition from a dense to a sparse curve pattern. Moreover, the symmetry of the hysteresis loop was lost in the later stages of shearing. With an increase in the number of cycles, the cumulative shear strain gradually increased, and the increase in the cyclic ratio of water content to stress reduced the number of cyclic shear cycles required to achieve failure, thereby accelerating the soil’s failure rate. A predictive formula was developed based on the experimental results to estimate the failure cycles as a function of the cyclic stress ratio and moisture content. Furthermore, the softening index decreased gradually with an increasing number of cycles, and a higher moisture content and cyclic stress ratio accelerated the soil’s softening process. It was observed that under the conditions of optimal moisture content, the soil exhibited a slower softening rate during the initial stage of shearing.

Resource recovery and regeneration strategies for spent lithium-ion batteries: Toward sustainable high-value cathode materials - Kunhong Gu; Chiharu Tokoro; Yutaro Takaya; Jiang Zhou; Wenqing Qin; Junwei Han (Waste Management, 2024)

Two new sesquiterpene lactones from the branches and leaves of Cinnamomum camphora chvar. Borneol - Zhiyong Xu; Tao Jiang; Wei Xiong; Chuanqi Xie; Yunfei Liu; Xiaodan Han; Xuefang Wen; Jianping Fu; Junwei Xu; Yongsheng Guo; Lei Wu (Phytochemistry Letters, 2024)

A novel WO3/ZnIn2S4/CoWO4 heterojunction for enhancement of photocatalytic degradation sparfloxacin: Dual S-scheme multi-charge transfer mode and Mechanistic pathway - Han Sun; Lei Wang; Xudong Wang; Yonghao Dong; Jie Ren; Junwei Xin; Ruosong Jing; Jiajun An (Journal of Environmental Chemical Engineering, 2024)

The relationship between plasma nickel concentrations and type 2 diabetes mellitus risk: A protective effect within a specific range - Yong Zhang; Junwei Cai; Zijun Yao; Han Zhang; Zhen Wang; Jinlin Lei; Huailan Guo (Journal of Trace Elements in Medicine and Biology, 2024)

Metagenomic insights into the diversity of 2,4-dichlorophenol degraders and the cooperation patterns in a bacterial consortium - Shunli Hu; Chuangchuang Xu; Yanghe Xie; Lu Ma; Qingfeng Niu; Guomin Han; Junwei Huang (Science of The Total Environment, 2024)

Innovative methodology for comprehensive utilization of arsenic-bearing neutralization sludge - Tianfu Zhang; Junwei Han; Liuyang Dong; Dianwen Liu; Fen Jiao; Wenqing Qin; Wei Liu (Journal of Environmental Management, 2024)

Frequency-specific functional difference between gyri and sulci in naturalistic paradigm fMRI - Liting Wang; Yang Yang; Xintao Hu; Shijie Zhao; Xi Jiang; Lei Guo; Junwei Han; Tianming Liu (Brain Structure and Function, 2024)

Physics inspired hybrid attention for SAR target recognition - Zhongling Huang; Chong Wu; Xiwen Yao; Zhicheng Zhao; Xiankai Huang; Junwei Han (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Leaf spot on cucumber caused by Stemphylium vesicarium newly reported in China - Xiaoyan Yu; Rui Han; Weiqian Zhang; Zhihua Li; Xue Zhang; Xiangjing Wang; Wensheng Xiang; Junwei Zhao (Crop Protection, 2023)

Effective extraction of nickel and cobalt from sintered nickel alloy via reduction roasting and leaching - Yongwei Wang; Xuejie Chang; Mengjun Chen; Wenqing Qin; Junwei Han (Minerals Engineering, 2023)

Closed-loop recycling of spent lithium-ion batteries based on selective sulfidation: An unconventional approach - Kunhong Gu; Xuesong Gao; Yuxin Chen; Wenqing Qin; Junwei Han (Waste Management, 2023)

Inhibition mechanism of α-glucosidase inhibitors screened from Tartary buckwheat and synergistic effect with acarbose - Lin Han; Huiqing Wang; Junwei Cao; Yunlong Li; Xiying Jin; Caian He; Min Wang (Food Chemistry, 2023)

Epicoccum sorghinum as leaf spot disease-causing pathogen in ginger (Zingiber officinale Rosc.) in China - Xiaoyan Yu; Zhihua Li; Rui Han; Weiqian Zhang; Jing Zhang; Weiyue Cao; Yue Ma; Xiangjing Wang; Junwei Zhao; Wensheng Xiang (Crop Protection, 2023)

Coupling annealed silver nanoparticles with a porous silicon Bragg mirror SERS substrate and machine learning for rapid non-invasive disease diagnosis - Shibin Han; Cheng Chen; Chen Chen; Lijun Wu; Xue Wu; Chen Lu; Xueqin Zhang; Peng Chao; Xiaoyi Lv; Zhenhong Jia; Junwei Hou (Analytica Chimica Acta, 2023)

Recovery of zinc and extraction of calcium and sulfur from zinc-rich gypsum residue by selective reduction roasting combined with hydrolysis - Tianfu Zhang; Junwei Han; Wei Liu; Fen Jiao; Wenhao Jia; Wenqing Qin (Journal of Environmental Management, 2023)

Facile separation and regeneration of LiFePO4 from spent lithium-ion batteries via effective pyrolysis and flotation: An economical and eco-friendly approach - Xuehu Zhong; Xiaohui Mao; Wenqing Qin; Hongbo Zeng; Guangjin Zhao; Junwei Han (Waste Management, 2023)

Prenatal exposure to perfluorooctane sulfonate alternatives and associations with neonatal thyroid stimulating hormone concentration: A birth cohort study - Zhongqiang Cao; Junwei Li; Meng Yang; Hongjian Gong; Feiyan Xiang; Hao Zheng; Xiaonan Cai; Shunqing Xu; Aifen Zhou; Han Xiao (Chemosphere, 2023)

Cellulomonas triticagri sp. nov., isolated from the rhizosphere soil of wheat (Triticum aestivum L.) - Chuanyu Han; Yuting Zhang; Bing Yu; Qiqi Shan; Junwei Zhao; Haoran Shi; Yuanyuan Tian; Yan Zhang; Chunyu Zhu; Wensheng Xiang (Archives of Microbiology, 2022)

Cortical development coupling between surface area and sulcal depth on macaque brains - Xiao Li; Songyao Zhang; Xi Jiang; Shu Zhang; Junwei Han; Lei Guo; Tuo Zhang (Brain Structure and Function, 2022)

A 168-year temperature recording based on tree rings and latitude differences in temperature changes in northeast China - Yangao Jiang; Yuting Cao; Junhui Zhang; Zhuo Li; Guoqiang Shi; Shijie Han; Cassius E. O. Coombs; Chuan Liu; Xiaoguang Wang; Junwei Wang; Lin Hao; Qi Xu; et al. (International Journal of Biometeorology, 2021)

Genetic changes and evolutionary analysis of canine circovirus - Lin Wang; Yifan li; Zhiyuan Guo; Ying Yi; Han Zhang; Haikun Shangguan; Chengshi Huang; Junwei Ge (Archives of Virology, 2021)

Microbacterium helvum sp. nov., a novel actinobacterium isolated from cow dung - Xiao Li; Lida Zhang; Fuyan Huang; Junwei Zhao; Han Wang; Yanjie Jiao; Lulu Qian; Xiangjing Wang; Wensheng Xiang (Archives of Microbiology, 2021)

Herbidospora solisilvae sp. nov., a novel cellulose-degrading actinobacterium isolated from forest soil - Mingying Yu; Rui Zhou; Jingjing Li; Liyuan Han; Han Wang; Siyu Zhang; Junwei Zhao; Xiangjing Wang; Jia Song; Wensheng Xiang (Antonie van Leeuwenhoek, 2021)

Tree ring width‐based January–March mean minimum temperature reconstruction from Larix gmelinii in the Greater Khingan Mountains, China since AD 1765 - Yangao Jiang; Chuan Liu; Junhui Zhang; Shijie Han; Cassius E. O. Coombs; Xiaoguang Wang; Junwei Wang; Lin Hao; Shengzhong Dong (International Journal of Climatology, 2021)
A ring‐width chronology of Larix gmelinii (LG) was developed in the northern Greater Khingan Mountains region of China. The response function analyses revealed that the local mean minimum temperature of January–March ( T 1–3 ) was the most limiting factor affecting the radial growth of LG trees. Based on correlation analysis, a reconstructed T 1–3 series from 1765 to 2013 was produced using standard ring‐width chronology. The reconstruction explained 41.2% of the total variance in recorded monthly mean minimum temperatures from 1960 to 2013. The reconstructed T 1–3 series had similar variability when compared with the May–September mean temperature reconstruction in Inner Mongolia (IM) and the February–March mean minimum temperature reconstruction in Yichun (YC). This reconstructed T 1–3 series also captured the severe snow disaster and cold wave events recorded from historical documents in Heilongjiang and Inner Mongolia. Spatial correlations between reconstructed series and gridded temperature data also provided a high level of confidence. In addition, significant relationships between the reconstructed T 1–3 series and the Pacific Decadal Oscillation (PDO), El Niño–Southern Oscillation (ENSO), North Atlantic Oscillation (NAO), solar activity, indicated that the T 1–3 variation might be influenced by large‐scale ocean–atmosphere interactions.

Chemical constituents from Glehnia littoralis and their chemotaxonomic significance - Shouwen Zhang; Fang Cheng; Li Yang; Jinxiang Zeng; Fengyu Han; Xiuling Yu; Yuye Zhu; Guoyue Zhong; Junwei He (Natural Product Research, 2020)

Prediction of exploration targets based on integrated analyses of source rock and simulated hydrocarbon migration direction: a case study from the gentle slope of Shulu Sag, Bohai Bay Basin, northern China - Changqing Ren; Fugui He; Xianzhi Gao; Dongsheng Wu; Wenli Yao; Jianzhang Tian; Huiping Guo; Yuanxin Huang; Li Wang; Han Feng; Junwei Li (Geosciences Journal, 2019)

Load Transfer of Offshore Open-Ended Pipe Piles Considering the Effect of Soil Plugging - Junwei Liu; Zhen Guo; Bo Han (Journal of Marine Science and Engineering, 2019)
Open-ended pipe piles have been increasingly used as the foundations for offshore structures. Considering the soil plugging effect, a novel analytical model is proposed in this paper to study the load transfer mechanism of open-ended pipe piles. A trilinear model for the external shaft friction was introduced, while a rigid plastic model was adopted to describe the load transfer at the pile-plug interface. Furthermore, an equilibrium equation of the soil plug was proposed, based on the hypothesis of a trilinear distribution of lateral earth pressure. The pile end resistance was analyzed by dividing it into two parts, i.e., the soil plug and pile annulus, the behaviors of which were described by the double broken line model. A calculation example was carried out to analyze the load transfer properties of the open-ended pipe piles. As a validation, similar load transfer processes of the open-ended pile were also captured in a newly built discrete element method model, mimicking the 100g centrifuge testing conditions.

Microbispora tritici sp. nov., a novel actinomycete isolated from a root of wheat (Triticum aestivum L.) - Chuanyu Han; Junwei Zhao; Bing Yu; Haoran Shi; Chen Zhang; Xiaowei Guo; Wensheng Xiang; Xiangjing Wang (Antonie van Leeuwenhoek, 2019)

Pseudonocardia tritici sp. nov., a novel actinomycete isolated from rhizosphere soil of wheat (Triticum aestivum L.) - Jia Song; Shiwen Qiu; Junwei Zhao; Chuanyu Han; Ying Wang; Xiujun Sun; Shanwen Jiang; Xiangjing Wang; Wensheng Xiang (Antonie van Leeuwenhoek, 2019)

Streptomyces monticola sp. nov., a novel actinomycete isolated from soil - Dongmei Li; Liyuan Han; Junwei Zhao; Hanxun Ju; Shanwen Jiang; Xiaowei Guo; Xiangjing Wang; Wensheng Xiang (Antonie van Leeuwenhoek, 2019)

Sphaerimonospora triticiradicis sp. nov., a novel actinomycete isolated from a root of wheat (Triticum aestivum L.) - Chuanyu Han; Jiangmeihui Hu; Junwei Zhao; Yuanyuan Tian; Shanwen Jiang; Xiaowei Guo; Wensheng Xiang; Xiangjing Wang (Antonie van Leeuwenhoek, 2019)

Analytical solution for vertical site response analysis and its validation - Junwei Liu; Xiao Zhang; Zewei Cao; Bo Han; Shizeng Yang (Earthquake Engineering and Engineering Vibration, 2019)

Streptomyces xiangluensis sp. nov., a novel actinomycete isolated from soil - Junwei Zhao; Dongmei Li; Hao Jiang; Liyuan Han; Shanwen Jiang; Xiaowei Guo; Xiangjing Wang; Wensheng Xiang (Antonie van Leeuwenhoek, 2018)

Promicromonospora viridis sp. nov., a novel actinomycete isolated from soil - Liying Jin; Junwei Zhao; Shanwen Jiang; Yang Zhao; Xiaoyang Han; Xiaowei Guo; Xiangjing Wang; Wensheng Xiang (Antonie van Leeuwenhoek, 2018)

Decoding Auditory Saliency from Brain Activity Patterns during Free Listening to Naturalistic Audio Excerpts - Shijie Zhao; Junwei Han; Xi Jiang; Heng Huang; Huan Liu; Jinglei Lv; Lei Guo; Tianming Liu (Neuroinformatics, 2018)

Nonomuraea lycopersici sp. nov., isolated from the root of tomato plants (Solanum lycopersicum L.) - Weiwei Zheng; Junwei Zhao; Dongmei Li; Hao Jiang; Liyuan Han; Xueli Zhao; Yufei Chen; Xiangjing Wang; Wensheng Xiang (Antonie van Leeuwenhoek, 2018)

Extendable supervised dictionary learning for exploring diverse and concurrent brain activities in task-based fMRI - Shijie Zhao; Junwei Han; Xintao Hu; Xi Jiang; Jinglei Lv; Tuo Zhang; Shu Zhang; Lei Guo; Tianming Liu (Brain Imaging and Behavior, 2018)

Commonly preserved and species-specific gyral folding patterns across primate brains - Xiao Li; Hanbo Chen; Tuo Zhang; Xiang Yu; Xi Jiang; Kaiming Li; Longchuan Li; Mir Jalil Razavi; Xianqiao Wang; Xintao Hu; Junwei Han; Lei Guo; et al. (Brain Structure and Function, 2017)

RETRACTED ARTICLE: Neural auditory intensity discrimination during naturalistic listening: a brain decoding study - Xintao Hu; Lei Guo; Junwei Han; Christine Cong Guo (Brain Structure and Function, 2017)

Decoding power-spectral profiles from FMRI brain activities during naturalistic auditory experience - Xintao Hu; Lei Guo; Junwei Han; Tianming Liu (Brain Imaging and Behavior, 2017)

Signal sampling for efficient sparse representation of resting state FMRI data - Bao Ge; Milad Makkie; Jin Wang; Shijie Zhao; Xi Jiang; Xiang Li; Jinglei Lv; Shu Zhang; Wei Zhang; Junwei Han; Lei Guo; Tianming Liu (Brain Imaging and Behavior, 2016)

Microbispora camponoti sp. nov., a novel actinomycete isolated from the cuticle of Camponotus japonicus Mayr - Chuanyu Han; Chongxi Liu; Junwei Zhao; Lifeng Guo; Chang Lu; Jiansong Li; Feiyu Jia; Xiangjing Wang; Wensheng Xiang (Antonie van Leeuwenhoek, 2016)

Actinomadura jiaoheensis sp. nov. and Actinomadura sporangiiformans sp. nov., two novel actinomycetes isolated from muddy soil and emended description of the genus Actinomadura - Junwei Zhao; Lifeng Guo; Pengyu Sun; Chuanyu Han; Lu Bai; Chongxi Liu; Yunxi Li; Wensheng Xiang; Xiangjing Wang (Antonie van Leeuwenhoek, 2015)

Data-driven analysis of functional brain interactions during free listening to music and speech - Jun Fang; Xintao Hu; Junwei Han; Xi Jiang; Dajiang Zhu; Lei Guo; Tianming Liu (Brain Imaging and Behavior, 2015)

Kribbella qitaiheensis sp. nov., a novel actinomycete isolated from soil - Lifeng Guo; Junwei Zhao; Chongxi Liu; Chuanyu Han; Lu Bai; Pengyu Sun; Jiansong Li; Xiangjing Wang; Wensheng Xiang (Antonie van Leeuwenhoek, 2015)

Effects of Olanzapine–Fluoxetine Combination Treatment of Major Depressive Disorders on the Quality of Life During Acute Treatment Period - Wei Qu; Shanshan Gu; Han Luo; Qianying Tang; Junwei Guo (Cell Biochemistry and Biophysics, 2014)

Identifying and Characterizing Resting State Networks in Temporally Dynamic Functional Connectomes - Xin Zhang; Xiang Li; Changfeng Jin; Hanbo Chen; Kaiming Li; Dajiang Zhu; Xi Jiang; Tuo Zhang; Jinglei Lv; Xintao Hu; Junwei Han; Qun Zhao; et al. (Brain Topography, 2014)

Group-Wise FMRI Activation Detection on DICCCOL Landmarks - Jinglei Lv; Lei Guo; Dajiang Zhu; Tuo Zhang; Xintao Hu; Junwei Han; Tianming Liu (Neuroinformatics, 2014)

Encoding brain network response to free viewing of videos - Junwei Han; Shijie Zhao; Xintao Hu; Lei Guo; Tianming Liu (Cognitive Neurodynamics, 2014)

Embelin Suppresses Dendritic Cell Functions and Limits Autoimmune Encephalomyelitis Through the TGF-β/β-catenin and STAT3 Signaling Pathways - Zhenyi Xue; Zhenzhen Ge; Kai Zhang; Rui Sun; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; Wen Li; Da Zhang; Junwei Hao; Yurong Da; et al. (Molecular Neurobiology, 2014)

Survey of encoding and decoding of visual stimulus via FMRI: an image analysis perspective - Mo Chen; Junwei Han; Xintao Hu; Xi Jiang; Lei Guo; Tianming Liu (Brain Imaging and Behavior, 2014)

A linear model for characterization of synchronization frequencies of neural networks - Peili Lv; Xintao Hu; Jinglei Lv; Junwei Han; Lei Guo; Tianming Liu (Cognitive Neurodynamics, 2014)

Fine-Granularity Functional Interaction Signatures for Characterization of Brain Conditions - Xintao Hu; Dajiang Zhu; Peili Lv; Kaiming Li; Junwei Han; Lihong Wang; Dinggang Shen; Lei Guo; Tianming Liu (Neuroinformatics, 2013)

Decreased expression of miR-126 correlates with metastatic recurrence of hepatocellular carcinoma - Hongyuan Chen; Ruizheng Miao; Junwei Fan; Zhongbo Han; Junyi Wu; Guoqiang Qiu; Huamei Tang; Zhihai Peng (Clinical & Experimental Metastasis, 2013)

Automatic landslide detection from remote-sensing imagery using a scene classification method based on BoVW and pLSA - Gong Cheng; Lei Guo; Tianyun Zhao; Junwei Han; Huihui Li; Jun Fang (International Journal of Remote Sensing, 2013)

Resting State fMRI-guided Fiber Clustering: Methods and Applications - Bao Ge; Lei Guo; Tuo Zhang; Xintao Hu; Junwei Han; Tianming Liu (Neuroinformatics, 2013)

Meta-Analysis of Functional Roles of DICCCOLs - Yixuan Yuan; Xi Jiang; Dajiang Zhu; Hanbo Chen; Kaiming Li; Peili Lv; Xiang Yu; Xiaojin Li; Shu Zhang; Tuo Zhang; Xintao Hu; Junwei Han; et al. (Neuroinformatics, 2013)

Individual Functional ROI Optimization Via Maximization of Group-Wise Consistency of Structural and Functional Profiles - Kaiming Li; Lei Guo; Dajiang Zhu; Xintao Hu; Junwei Han; Tianming Liu (Neuroinformatics, 2012)

Adaptive inverse control of random vibration based on the filtered-X LMS algorithm - Zhidong Yang; Qitao Huang; Junwei Han; Hongren Li (Earthquake Engineering and Engineering Vibration, 2010)

Characterization of the gene encoding glycoprotein C of duck enteritis virus - Fengyuan Liu; Bo Ma; Yan Zhao; Yang Zhang; Yi Han Wu; XiaoMei Liu; JunWei Wang (Virus Genes, 2008)